2020
DOI: 10.1021/acsami.0c16899
|View full text |Cite
|
Sign up to set email alerts
|

Will Sulfide Electrolytes be Suitable Candidates for Constructing a Stable Solid/Liquid Electrolyte Interface?

Abstract: Conversion-type batteries with electrode materials partially dissolved in liquid electrolyte exhibit high specific capacity and excellent redox kinetics, but currently poor stability due to the shuttle effect. Using solid-electrolyte separator to block the mass exchange between cathode and anode can eliminate the shuttle effect. A stable interface between the solid-electrolyte separator and the liquid electrolyte is essential for the battery performance. Here we demonstrate that a stable interface with low int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…It can be observed that there are two peaks corresponding to the C−O‐La (533.0 eV) and S−O (531.9 eV) [33,34] . For the S 2p peak (Figure 5g), the peak at 161.6, 163.0, 166.3, 168.4 and 169.5 eV are ascribed to the terminal sulfur atoms (S −1 ), bridging sulfur atoms (S 0 ), SO 3 − , SO 4 − and SO x −1 during the discharge mechanism, which could alleviate the sever shuttle problem [35,36,37] . Besides this, a new overlapped peak emerged at 163.5 eV, referring to the S−La chemical interactions [38] .…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that there are two peaks corresponding to the C−O‐La (533.0 eV) and S−O (531.9 eV) [33,34] . For the S 2p peak (Figure 5g), the peak at 161.6, 163.0, 166.3, 168.4 and 169.5 eV are ascribed to the terminal sulfur atoms (S −1 ), bridging sulfur atoms (S 0 ), SO 3 − , SO 4 − and SO x −1 during the discharge mechanism, which could alleviate the sever shuttle problem [35,36,37] . Besides this, a new overlapped peak emerged at 163.5 eV, referring to the S−La chemical interactions [38] .…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27] Therefore, a new-configuration battery with Li 1.5 Bp 3 (DME) 10 anode and sulfide solid electrolyte may promote a high power-density energy storage device with essentially suppressed lithium-dendrite nucleation and growth. However, sulfide SEs will decompose in organic solvents with high polarity, [28][29][30] making the chemical stability between sulfide SE and organic liquid anode first priority before assembling the battery.…”
Section: J(t) Expmentioning
confidence: 99%
“…However, the lithium dendrite can also form in a battery with solid-liquid hybrid electrolyte. [28] For Li-Bp-DME anode, the most important and unique property is that it is a kind of solvated electron solution in which Li-ions can interact with biphenyl radical anions and form stable [(Bp• − )Li + ](C 4 H 10 O 2 ) structure [50] during lithium plating. That means solid lithium metal will not appear in the liquid anode solution, so that Li dendrite nucleation and growth at electrode/electrolyte interface or inside the SSE are ultimately suppressed.…”
Section: J(t) Expmentioning
confidence: 99%
“…Firstly, β-Li3PS4/S composite was prepared by dual-solution synthesis as described in our previous study. [13] Briefly, tetrahydrofuran solution of Li2S6 and acetonitrile solution of Li2S•P2S5 were prepared by stirring the raw materials (Li2S and S for Li2S6, Li2S and P2S5 for Li2S•P2S5) in the solvents, and then two solutions were mixed. The precursor solution was dried at 60 °C to remove the excess solvent and further heat-treated at 230 °C under argon for 1 h to obtain the products.…”
Section: Accepted Manuscriptmentioning
confidence: 99%